2012
DOI: 10.2147/ijn.s27621
|View full text |Cite|
|
Sign up to set email alerts
|

Controlled-release and preserved bioactivity of proteins from (self-assembled) core-shell double-walled microspheres

Abstract: Abstract:In order to address preserved protein bioactivities and protein sustained-release problems, a method for preparing double-walled microspheres with a core (protein-loaded nanoparticles with a polymer-suspended granule system-formed core) and a second shell (a polymerformed shell) for controlled drug release and preserved protein bioactivities has been developed using (solid-in-oil phase-in-hydrophilic oil-in-water (S/O/O h /W)) phases. The method, based on our previous microsphere preparation method (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…[1][2][3][4][5] Yin and Yates reported that drug-entrapped biodegradable microcapsules, with sustained drug release, were prepared by spraying a suspension of hollow poly(DL-lactide) particles in procaine hydrochloride aqueous solution into plasticizing solvents. 6 A further report by Zvonar et al described use of a self-microemulsifying system to fabricate Ca-pectinate microcapsules to improve the release and permeability of furosemide.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Yin and Yates reported that drug-entrapped biodegradable microcapsules, with sustained drug release, were prepared by spraying a suspension of hollow poly(DL-lactide) particles in procaine hydrochloride aqueous solution into plasticizing solvents. 6 A further report by Zvonar et al described use of a self-microemulsifying system to fabricate Ca-pectinate microcapsules to improve the release and permeability of furosemide.…”
Section: Introductionmentioning
confidence: 99%
“…25,37 The mixture was stirred at 2000 rpm for 20-30 seconds at 0°C, and then the mixture solution was kept in the refrigerator at −80°C for up to 12 hours. The samples were freeze-dried with Christ (Osterode, Germany) Alpha 1-2 laboratory freeze-drying equipment at 5.25 × 10 −3 Pa pressure for 24 hours.…”
Section: Preparation Of G-csf-loaded Dextran Nanoparticlesmentioning
confidence: 99%
“…The solidified microspheres were washed three times using distilled water and then freeze-dried again before storage (Figure 1). 37 Preparation for G-CSF-loaded PLGA microspheres using W/O/W As control, G-CSF was microencapsulated into PLGA microspheres through a conventional water-in-oil-in-water (W/O/W) method. The 0.1-mL G-CSF water solution (containing 0.25% w/w G-CSF) was added into 0.9 mL PLGA DCM solution (containing 10% w/w PLGA) under stirring with a Fluko FA25 homogenizer at 5000 rpm to prepare a water-in-oil primary emulsion.…”
Section: Preparation Of Dextran Nanoparticle-loaded Microspheresmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously developed various preparation methods for biological molecular protein drug delivery such as the waterin-oil-in-hydrophilic oil-in-water (W/O/hO/W) method (34), solid-in-oil-in-oil-in-water (S/O/O/W) method (35)(36)(37), and solid-in-oil-in-hydrophilic oil-in-ethanol (S/O/hO/E) method (38,39,40). The chemical agents were not microencapsulated in the microspheres using these preparation methods.…”
Section: Introductionmentioning
confidence: 99%